2004
DOI: 10.1051/0004-6361:20035896
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of vertical shear instability in accretion discs

Abstract: Abstract. The nonlinear evolution of the vertical shear instability in accretion discs is investigated using three-dimensional hydrodynamic simulations. A vertical dependence of the angular velocity destabilizes the disc and leads to the generation of velocity fluctuations enhancing the angular momentum transport. The instability emerges in the numerical models for large radial perturbation wave numbers. The growth time is a few tens of orbital revolutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 25 publications
5
52
0
Order By: Relevance
“…How robust is the VSI to different radial boundary conditions, and how do these vouch for the true conditions of protoplanetary disk dead zones? As observed by Urpin (2003) and Arlt & Urpin (2004), the local growth rates of the VSI scale approximately by Ω 0 . While it has not yet been theoretically established to what degree the VSI is active in disk regions that also support the MRI, it is worthwhile noting that the growth rate of the VSI (when active in the absence of the MRI) is a factor of slower than the MRI underscoring the differing timescales of the two instabilities.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…How robust is the VSI to different radial boundary conditions, and how do these vouch for the true conditions of protoplanetary disk dead zones? As observed by Urpin (2003) and Arlt & Urpin (2004), the local growth rates of the VSI scale approximately by Ω 0 . While it has not yet been theoretically established to what degree the VSI is active in disk regions that also support the MRI, it is worthwhile noting that the growth rate of the VSI (when active in the absence of the MRI) is a factor of slower than the MRI underscoring the differing timescales of the two instabilities.…”
Section: Discussionsupporting
confidence: 57%
“…The vertical shear instability (VSI; Urpin 2003; Urpin & Brandenburg 1998;Arlt & Urpin 2004;Nelson et al 2013;McNally & Pessah 2015;Stoll & Kley 2015), also known as the Goldreich Schubert Fricke instability (Goldreich & Schubert 1967;Fricke 1968) is a linear instability of axisymmetric inertial modes that relies on the vertical shear of the basic near-Keplerian flow state. This instability may be active in non-magnetized parts of protoplanetary accretion disks and is perhaps discernible in their dead zones (Turner et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The first authors analysed the instability for globally isothermal discs and found that the instability in this case could only be triggered by applying finite initial perturbation because the equilibrium state of the disc (being strictly isothermal) did not contain a shear in Ω. The maximum values of α obtained by Arlt & Urpin (2004) were around 6 × 10 −6 , but the turbulence was decaying in the long run. Nelson et al (2013) extended these simulations and performed high resolution simulations of the VSI for so-called locally isothermal discs that contain a radial temperature gradient, but are vertically isothermal.…”
Section: Introductionmentioning
confidence: 99%
“…Local stability analyzes (Klahr 2004;Johnson & Gammie 2005a) find transient instability in this context, but shearing box simulations indicate that this does not drive turbulence (Johnson & Gammie 2005b). Urpin (2003) discusses an instability related to vertical shear and heat transport of the Goldreich-Schubert type (Goldreich & Schubert 1967); however, this instability produces only a rather weak radial transport (Arlt & Urpin 2004). More recently, Dubrulle et al (2005b) and Shalybkov & Ruediger (2005) have discussed an instability arising when both the fluid differential rotation and vertical stratification are stabilizing according to the Høiland criterion.…”
Section: Introductionmentioning
confidence: 99%